PENGARUH KEPRIBADIAN SISWA TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VII SMPN 254 JAKARTA - Andrey Santoso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of students’ personality types on their understanding of mathematical concepts in algebra among seventh-grade students at SMPN 254 Jakarta. The research method used was a quantitative method with an ex post facto approach. The instruments used in this study were a mathematical concept comprehension test and a personality type questionnaire. The research sample consisted of 100 seventh-grade students at SMPN 254 Jakarta, comprising students with sanguine, choleric, phlegmatic, and melancholic personality types. Data analysis techniques included normality tests, homogeneity tests, one-way ANOVA, and Bonferroni post hoc tests. The results indicate that personality type influences students’ understanding of mathematical concepts, as evidenced by a significance value of 0.004 < 0.05. The post hoc test results showed that there were significant differences between the melancholic and sanguine personality types, as well as between the phlegmatic and sanguine personality types. Thus, it can be concluded that personality type influences the level of mathematical concept understanding among seventh-grade students at SMPN 254 Jakarta.